The Current State of Normative and Legal Regulation of Bankruptcy Procedures in Ukraine - V. B. Pchelin (Bulletin of Kharkiv National University of Internal Affairs)
It has been emphasized that one of the means of overcoming the financial crisis is a properly functioning institution of bankruptcy. It has been found out that the efficiency of bankruptcy proceedings in Ukraine is low, due to the long duration of such a procedure and its high cost. The national legislation regulating bankruptcy procedures in Ukraine has been analyzed. Comparative and legal analysis of the Bankruptcy Procedure Code of Ukraine and other normative and legal acts regulating the scope of restoring the solvency of the debtor or his recognition as a bankrupt has been carried out. The contradictory and sometimes radically conflicting provisions of the Bankruptcy Procedure Code of Ukraine have been determined. It has been established that, although the Bankruptcy Procedure Code of Ukraine was adopted not so long ago, and it came into force almost a year ago, it was amended several times. It is evidence of improper normative and legal regulation of bankruptcy procedures, which, in particular, finds its manifestation in the absence of stability in the functioning of this sphere of public relations. It has been noted that the name of the Bankruptcy Procedure Code of Ukraine requires adjustment in regard its change into the Code of Ukraine on Procedures for Restoring the Debtor’s Solvency or Declaring Him Bankrupt, which will fully comply with the subject matter of its normative and legal regulation. Particular attention has been paid to the provisions of the Bankruptcy Procedure Code of Ukraine, which determine the features of its entry into force. It turns out that the Bankruptcy Procedure Code of Ukraine was in force for six months, but not enacted, which is a complete disregard for legal techniques. The instructions of the Bankruptcy Procedure Code of Ukraine on determining the features of normative and legal regulation of legal relations in the field of bankruptcy procedures have been analyzed. The author has suggested the following wording of Part 1 of the Art. 2 of the Bankruptcy Procedure Code of Ukraine: “Bankruptcy proceedings are regulated by the Constitution of Ukraine, International Treaties of Ukraine, the binding nature of which is approved by Verkhovna Rada of Ukraine, this Code, the Commercial Procedural Code of Ukraine and other laws of Ukraine”.